Development of Digital Flashcard Learning Media Assisted by Quizlet Based on Contextual Teaching and Learning (CTL) Oriented to Critical Thinking Skills on Electrolyte and Non-Electrolyte Solution Material - Riris Desinta Marsaulina Manalu; Wilda Syahri; Muhammad Haris Effendi Hasibuan; Haryanto Haryanto; Zurweni Zurweni (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Chemistry learning on electrolyte and non-electrolyte solutions is still abstract and difficult to visualize, so it requires digital learning media that can encourage active student involvement in critical thinking. This study aims to develop digital flashcard learning media assisted by Quizlet, based on Contextual Teaching and Learning (CTL), that are oriented towards critical thinking skills, to assess the feasibility of the media, teacher assessment, student responses, and to provide an overview of students' critical thinking skills after using the developed media. This research is a research and development (R&D) with the Lee & Owens model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were grade XII high school students. The research instruments included validation sheets from material experts and media experts, teacher assessment questionnaires, student response questionnaires, and evaluation tests. Data were analyzed descriptively, quantitatively, and qualitatively. The results showed that material expert validation increased from 85% to 97% after revision, media expert validation increased by 90%, and teacher assessment increased by 90%, with a very feasible category. Student responses in the one-to-one trial were 86.6%, and in the small group trial were 86.25%, categorized as very good. The evaluation results, at 82.27%, indicate that students' understanding is in the very good category. Therefore, the digital flashcard learning media, supported by Quizlet and based on CTL, is highly suitable as an alternative learning medium for high school chemistry and has the potential to foster students' critical thinking skills.